Relative prices, trading gains, and real GDI: The case of Canada - Yi Zheng (Bank of Canada, 2009)
Treating imports as intermediate inputs to domestic production, the author adopts the translog function approach to model real gross domestic income (GDI) in Canada over the 19612006 period. She explores the role of price ratios, such as terms of trade and the real effective exchange rate, in explaining changes in real GDI, trade openness, trade balance, and labour share of income, after controlling for factor endowments and technological improvements. Models are developed for both the total economy and the business sector, with alternative assumptions about the flexibility of labour input, user cost of capital, and the representation of technological changes.
Keywords: F10; O47; C43; D33; 330; Productivity; Econometric and statistical methods; Volkseinkommen; Terms of Trade; Wechselkurs; Produktivität; Internationaler Wettbewerb; Ökonometrisches Modell; Kanada